2020
DOI: 10.1002/alz.12104
|View full text |Cite
|
Sign up to set email alerts
|

Tau and apolipoprotein E modulate cerebrovascular tight junction integrity independent of cerebral amyloid angiopathy in Alzheimer's disease

Abstract: Introduction: Cerebrovascular pathologies including cerebral amyloid angiopathy (CAA) and blood-brain barrier (BBB) dysregulation are prominent features in the majority of Alzheimer's disease (AD) cases. Methods: We performed neuropathologic and biochemical studies on a large, neuropathologically confirmed human AD cohort (N = 469). Amounts of endothelial tight junction proteins claudin-5 (CLDN5) and occludin (OCLN), and major AD-related molecules (amyloid beta [A 40], A 42, tau, p-tau, and apolipoprotein E) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 60 publications
9
57
0
Order By: Relevance
“…With the increase in age, the aging scores in both disease and normal aged individuals showed an upward trend. The results also showed that the accelerated aging pattern in ND compared with the normal aged people, which was consistent with previous studies ( Liu et al, 2020 ). Compared with the chronological age, the aging score was more informative.…”
Section: Resultssupporting
confidence: 93%
“…With the increase in age, the aging scores in both disease and normal aged individuals showed an upward trend. The results also showed that the accelerated aging pattern in ND compared with the normal aged people, which was consistent with previous studies ( Liu et al, 2020 ). Compared with the chronological age, the aging score was more informative.…”
Section: Resultssupporting
confidence: 93%
“…Several experimental studies have shown that modelling of cerebral hypoperfusion increases tau phosphorylation: in adult Wistar rats [108], transgenic mice with Aβ and tau accumulation [109], and rat and human brain slices exposed to oxygen and glucose deprivation [110]. In a recent autopsy study, elevated levels of soluble tau and insoluble phosphotau were associated with lower levels of endothelial tight junction proteins, claudin-5 and occludin, in AD [111]. Tau-overexpressing mice were shown to have abnormal blood vessel morphology and increased vessel density [112].…”
Section: The Types Of Cerebral Ischaemic Damage Seen In Covid-19 Are mentioning
confidence: 99%
“…CBF reduction is a typical phenotype in AD patients and relates to cognitive decline [ 71 ]. In addition, tau is associated with TJ proteins reduction in the cortical region of AD brains [ 72 ]. According to these studies, it is clear that tau/NFT induces blood vessels morphology changes and vascular dysfunction.…”
Section: Blood–brain Barrier Dysfunction In Neurodegenerative Diseasesmentioning
confidence: 99%